# Solve for u -10/(u-3)=5/(u+9) -10u-3=5u+9
Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.
(-10)⋅(u+9)=(u-3)⋅5
Solve the equation for u.
Simplify (-10)⋅(u+9).
Apply the distributive property.
-10u-10⋅9=(u-3)⋅5
Multiply -10 by 9.
-10u-90=(u-3)⋅5
-10u-90=(u-3)⋅5
Simplify (u-3)⋅5.
Apply the distributive property.
-10u-90=u⋅5-3⋅5
Simplify the expression.
Move 5 to the left of u.
-10u-90=5⋅u-3⋅5
Multiply -3 by 5.
-10u-90=5u-15
-10u-90=5u-15
-10u-90=5u-15
Move all terms containing u to the left side of the equation.
Subtract 5u from both sides of the equation.
-10u-90-5u=-15
Subtract 5u from -10u.
-15u-90=-15
-15u-90=-15
Move all terms not containing u to the right side of the equation.
Add 90 to both sides of the equation.
-15u=-15+90
Add -15 and 90.
-15u=75
-15u=75
Divide each term by -15 and simplify.
Divide each term in -15u=75 by -15.
-15u-15=75-15
Cancel the common factor of -15.
Cancel the common factor.
-15u-15=75-15
Divide u by 1.
u=75-15
u=75-15
Divide 75 by -15.
u=-5
u=-5
u=-5
Solve for u -10/(u-3)=5/(u+9)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top